Not a Forest but a Neon Technological Urban Tree (On the Exhibition In Front of Me, 2020) - Zankov, Ventsislav (Sledva : NBU Journal of Humanities and Arts, 2020)
The author’s exhibition In Front of Me is a visual symbiosis of two themes: two crises intertwined in the human behavior – the ecological one and the social one borne by the pandemic situation that turns into a deeper existential crisis and questioning of the human. The trees represented in large-scale paintings are not a forest but rather some singular entities, bare-stripped crowns strenuously cut into a gloomy sky.